Photocatalytic degradation of cephalexin by g-C3N4/Zn doped Fe3O4 under visible light. Issue 8 (3rd April 2021) - Nguyen, Xuan Sang; Pham, Tien Dung; Vo, Hoang Tung; Ngo, Kim Dinh
ABSTRACT: In this work, we reported synthesis of a novel magnetically separable g-C3 N4 /Zn doped Fe3 O4 composite (g-CN/ZnFe) by a simple polyol thermal method. The characteristics of the as-prepared composite was checked by XRD, SEM, TEM, XPS, PL technologies. The optimized weight ratio of g-C3 N4 and Zn doped Fe3 O4 was investigated. In addition, the photocatalytic activities of the composite products were checked by degradation of Cephalexin (CEX) under visible light. The results showed that g-CN/ZnFe composite with an added 20% g-C3 N4 exhibited the highest photocatalytic activity for cephalexin under visible light irradiation. The improved photocatalytic activity of 20% g-CN/ZnFe can be ascribed to the low combination rate of photoinduced electron/hole pairs. Especially, g-CN/ZnFe can be recovered easily by using an external magnetic field and has the high stability after six runs. These properties of the g-CN/ZnFe as-prepared composite could be a promising photocatalyst for the degradation of pharmaceutical contaminants. GRAPHICAL ABSTRACT: UF0001